Oxidation behavior of Ti-Zr-Ni-Cu metallic glass. (February 2020) - Na, Min Young; Kim, Yong Joo; Kim, Won Tae; Kim, Do Hyang
Highlights: Oxidation of TiNi-based metallic glass during continuous heating is investigated. The oxide of Ti40 Zr10 Ni40 Cu10 metallic glass forms a layered structure. The difference in diffusivity between undercooled liquid and crystalline phase changes the growth mode of internal oxidation. Abstract: Oxidation behavior during continuous heating of Ti40 Zr10 Ni40 Cu10 metallic glass in a dry air has been studied by a combination of thermal analysis, thermogravimetric analysis (TGA) and detailed structural analysis using STEM and TEM. With increasing temperature, three different types of oxide growth took place: amorphous Ti(Zr) oxide formation with Ni enrichment beneath the oxide layer on glass substrate; Crystallization of Ni enriched amorphous layer into Ni3 Ti structure, followed by oxide growth with lamellar structure consisted of Ti(Zr) amorphous oxide and Ni3 Ti until crystallization of matrix; oxide growth with particulate structure in crystalline substrate.